Ensuring both velocity and spatial responses robust to B0/B1+ field inhomogeneities for velocity‐selective arterial spin labeling through dynamic phase‐cycling. Issue 5 (8th December 2020) - Liu, Dapeng; Li, Wenbo; Xu, Feng; Zhu, Dan; Shin, Taehoon; Qin, Qin
Abstract : Purpose: To evaluate both velocity and spatial responses of velocity‐selective arterial spin labeling (VS‐ASL), using velocity‐insensitive and velocity‐compensated waveforms for control modules, as well as a novel dynamic phase‐cycling approach, at different B0 / B 1 + field inhomogeneities. Methods: In the presence of imperfect refocusing, the mechanism of phase‐cycling the refocusing pulses through four dynamics was first theoretically analyzed with the conventional velocity‐selective saturation (VSS) pulse train. Numerical simulations were then deployed to compare the performance of the Fourier‐transform based velocity‐selective inversion (FT‐VSI) with these three different schemes in terms of both velocity and spatial responses under various B0 / B 1 + conditions. Phantom and human brain scans were performed to evaluate the three methods at B 1 + scales of 0.8, 1.0, and 1.2. Results: The simulations of FT‐VSI showed that, under nonuniform B0 / B 1 + conditions, the scheme with velocity‐insensitive control was susceptible to DC bias of the static spins as systematic error, while the scheme with velocity‐compensated control had deteriorated velocity‐selective labeling profiles and, thus, reduced labeling efficiency. Through numerical simulation, phantom scans, and brain perfusion measurements, the dynamic phase‐cycling method demonstrated considerable improvements over these issues. Conclusion: The proposed dynamic phase‐cycling approach was demonstrated for the velocity‐selective label and control modules with both velocity and spatial responses robust to a wide range of B0 and B 1 + field inhomogeneities.